Applying Multi-Objective Evolutionary Computation for Optimal Feng Shui Layout in Interior Design - Lu Chiang, Ting; Juan, Yi-Kai; Lee, Chao-Chiung (International Journal of Architectural Engineering Technology, 2024)
Feng Shui principles have a profound impact in Asia, studies have shown that consumers often consider Feng Shui when purchasing property to arrange interior layouts. Balancing design requirements and cultural beliefs in the design process requires significant communication and calculation efforts, However, aside from repeated communication among Feng Shui experts, homeowners, and designers, there is currently a lack of efficient methods to incorporate Feng Shui into design. Therefore, this study establishes a decision model to provide layout recommendations for purchase property, design, and for existing property renovation planning. By references Feng Shui Compass School principles to assess the Feng Shui quality of dwelling interiors and considers spatial layout and area distribution rules to evaluate the feasibility of the solution. Multi-Objective Evolutionary Algorithm (MOEA) is then applied to optimize Feng Shui and design conditions in real-world case studies. The results show that the application can effectively optimize and balance Feng Shui and design conditions in a short period of time, also provides homeowners and designers with clear strategies during purchase, design, and renovation to meet the needs related to cultural beliefs.